Refining items for a preference-based, amyotrophic lateral sclerosis specific, health-related quality of life scale. Issue 7 (2nd October 2022) - Van Damme, Jill; Kuspinar, Ayse; Johnston, Wendy; O'Connell, Colleen; Turnbull, John; Chum, Marvin; Strachan, Patricia; Luth, Westerly; McCullum, Shane; Peters, Nicole; MacDermid, Joy; Dal Bello-Haas, Vanina
Abstract: Objective: The aim of this study was to refine the items of a preference-based amyotrophic lateral sclerosis health-related quality of life scale (PB-ALS HRQL scale) based on domains generated in a previous study. Methods: Survey methodology was used to assess item importance rating (IR) and independence. Median importance was calculated for each item and a rating of "very important" was required for the item to remain. Correlations were used to examine item independence. Highly correlated items ( rs > 0.7) were considered for removal. Cognitive debriefing (CD) interviews, conducted by Zoom, telephone, or email based on participant preference and communication needs, were used to identify potential issues. Participants provided feedback about wording, clarity, response options, and recall period on randomly selected items. Items were considered finalized when three sequential CD participants approved the item with no revisions. Results: Thirty-four people with ALS (PALS, n = 16 females; age range 44–78 years; ALS Functional Rating Scale-Revised [ALSFRS-R] range 0–48) in Canada completed the survey; a subset of 18 PALS completed CD interviews ( n = 8 female; age range 44–71 years; ALSFRS-R range 0–48). Four items were highly correlated with one or more items, were not rated as very important, or were not approved via CD and were removed. Conclusions: The final four-response option PB-ALS Scale includes eight items: recreation and leisure, mobility, interpersonal interactions and relationships, eating and swallowing, handling objects, communicating, routine activities, and mood. The next step is to translate the PB-ALS Scale into French and develop a scoring algorithm based on PALS' preferences.